2017
DOI: 10.1142/s1793545817500122
|View full text |Cite
|
Sign up to set email alerts
|

Near infra-red light treatment of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disease. The symptoms include memory and spatial learning di±culties, language disorders, and loss of motivation, which get worse over time, eventually ending in death. No e®ective treatments are available for AD, currently. Current treatments only attenuate symptoms temporarily and are associated with severe side e®ects. Near infra-red (NIR) light has been studied for a long time. We investigated the e®ect of NIR on AD using a transgenic mouse model, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…We also tested the 1070-nm light pulsed at 40 Hz, with the same average power density and total fluence applied to compare the differences of therapeutic effects influenced only by the pulse frequency of light. Based on previous results 25 , the wavelength of the LED array was chosen as 1070 ± 50 nm, and the average power density was 25 mW/cm 2 . The transmittances of incident 1070-nm light were summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also tested the 1070-nm light pulsed at 40 Hz, with the same average power density and total fluence applied to compare the differences of therapeutic effects influenced only by the pulse frequency of light. Based on previous results 25 , the wavelength of the LED array was chosen as 1070 ± 50 nm, and the average power density was 25 mW/cm 2 . The transmittances of incident 1070-nm light were summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is compelling evidence suggested that PBM is capable of decreasing Aβ burden in the plasma 17 , cerebrospinal fluid 17 , and brain 19 in AD models. A previous study from our group demonstrated the therapeutic effects of continuous-wave light with a wavelength of 1070 nm on memory abilities and Aβ burden in an AD mouse model 25 . Similarly, Grillo et al demonstrated the beneficial effects of 1070-nm light on Aβ and phosphorylated tau protein levels in the brains of AD mice 15 .…”
Section: Introductionmentioning
confidence: 91%
“…As for the studies described in the results and referring to those that used animal models, the photobiomodulation, with the different protocols tested, brought together some results. Results described in in vivo studies using animal models showed reduction of hyper phosphorylation of the tau protein, attenuation of neurofibrillary tangles, decreased oxidative stress markers, reduced deposition, number, and size of β-amyloid plaques, reduced neuronal loss, formaldehyde dehydrogenase activation, positive influence on the flow of interstitial fluids, and capacity to recover and improve cognitive functions, such as learning and spatial memory capacity [30][31][32][33][34].…”
Section: Transcranial Photobiomodulationmentioning
confidence: 94%
“…Han et al [31] used animal model C57BL/6 J, being females divided into 3 groups: rats without irradiation (n = 10), rats with irradiation (n = 10), and normal rats without irradiation (n = 12). The therapeutic adopted was LED with wavelengths between 1040 nm and 1090 nm, power of 15 mW/cm2; 6 minutes a day, for 40 days, suspended for 28 days, and then starting the treatment again for another 15 days.…”
Section: Transcranial Photobiomodulation (Using Led)mentioning
confidence: 99%
“…The studies on using visible and near infrared light have suggested that these non-pharmacological and noninvasive treatments have the potential to improve AD due to their ability to alleviate pathology and cognitive dysfunction in AD mice [ 23 26 ]. As we know, sunlight has three major components: ultraviolet light, visible light and infrared radiation [ 27 ], and these lights also have multiple sub-divisions, such as near infrared light, middle infrared light and far infrared light.…”
Section: Introductionmentioning
confidence: 99%